Radiotherapy in Slovenia - Oblak, Irena; Anderluh, Franc (Onkologija : Slovenian Journal of Oncology, 2017)
Treatment with irradiation or radiotherapy is one of the three basic cancer treatment methods. In Slovenia, radiotherapy is carried out at the Institute of Oncology in Ljubljana and since November 2016 in a lesser extent also at the Department of Radiotherapy in the University Medical Centre in Maribor. In recent years in Slovenia, we performed on average over 6,000 teletherapy procedures in approximately 5,000 patients, and also around 400 brachytherapy procedures annually. This paper shows the current situation in the field of radiotherapy in Slovenia and also, based on the results of several international studies, where our current hardware and personnel capacities in this area put us in the European scale.